Trophic responsiveness of purified postnatal and adult rat retinal ganglion cells. - Ma, C; Taylor, J (2010)
Central neurons lose the ability for axonal re-growth during development and typically do not regenerate their axons following axotomy once they become mature unless given a growth-permissive environment i.e. peripheral nerve graft. In the present study, the growth responsiveness of purified retinal ganglion cells (RGCs) at different ages to neurotrophic factors and Schwann cell (SC)-secreted factors were examined directly. The purity of adult RGCs was 97% as assessed by retrograde labelling with 4,6-diamidino-2-phenylindole. The stability of cultures were demonstrated by long-term survival (30 days) in medium contained brain-derived neurotrophic factor (BDNF), ciliary neurotrophic factor (CNTF) and forskolin (F) (BCF). RGCs from postnatal (P) (P0, P4, P8, P21) and adult (P90) rats showed decreasing levels of survival and neuritogenesis when grown in BCF. In contrast, the opposite was observed in SC-conditioned medium (CM)-treated P0-P8 RGCs which were increasingly responsive. SCCM induced maximal neurite outgrowth in P8 RGCs via the activation of extracellular regulated kinase 1/2 (Erk1/2). Inhibition of mitogen-activated protein kinase-Erk1/2 signaling using an Erk1/2-specific inhibitor (UO126) abolished SCCM-induced Erk1/2 phosphorylation and neuritogenesis completely. Although both SCCM and BCF failed to sustain the same levels of growth in P21 or P90 cultures as observed in P8 cultures, SCCM promoted higher survival and neuritogenesis than BCF-treated adult RGCs. This study is the first report of adult rat RGC purification and demonstrates that mature RGCs need multiple factors for survival and neurite outgrowth.